INTERNET APPLICATIONS AND SOCIAL SKILLS AS CORRELATES OF TEACHERS’ EFFECTIVENESS IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE, NIGERIA - Ifeanyi, Peace Glory; Ezeaku, Stella (Int'l Journal of Education Research and Scientific Development, 2024)
The study investigated internet applications and social skills as correlates of teachers’ effectiveness in public secondary schools in Anambra State Nigeria. Two research questions and null hypotheses were tested at 0.05 level of significance. Literature related to the study were reviewed which exposed the need for the study. Correctional design was adopted using a total population of 571 public secondary school teachers in the area of the study. The instruments for data collection were researcher’s structured questionnaire. Cronbach Alpha method was used to establish the reliability of the instrument. The overall reliability indexes obtained were 0.83 and 0.85. Data collected were analyzed using Pearson Product Moment Statistics to answer the research questions and to test the null hypotheses at 0.05 level of significant. Statistical Package for Social Sciences (SPSS) was used to analyze the data collected. The study results showed that Microsoft team application had a high positive significant correlation with teachers’ effectiveness. Communication skill had a high positive significant correlation with teachers’ effectiveness. Based on the findings, there is need for evaluation and monitoring of internet applications, social skills and teachers’ effectiveness. This formal process would help foster principle of accountability within public school setting and improve teachers’ level of effectiveness.